Elimination of Ribosome Inactivating Factors Improves the Efficiency of Bacillus subtilis and Saccharomyces cerevisiae Cell-Free Translation Systems - Brodiazhenko, Tetiana; Johansson, Marcus J. O.; Takada, Hiraku; Nissan, Tracy; Hauryliuk, Vasili; Murina, Victoriia (Frontiers in Microbiology, 2018)
Cell-free translation systems based on cellular lysates optimized for in vitro protein synthesis have multiple applications both in basic and applied science, ranging from studies of translational regulation to cell-free production of proteins and ribosome-nascent chain complexes. In order to achieve both high activity and reproducibility in a translation system, it is essential that the ribosomes in the cellular lysate are enzymatically active. Here we demonstrate that genomic disruption of genes encoding ribosome inactivating factors – HPF in Bacillus subtilis and Stm1 in Saccharomyces cerevisiae – robustly improve the activities of bacterial and yeast translation systems. Importantly, the elimination of B. subtilis HPF results in a complete loss of 100S ribosomes, which otherwise interfere with disome-based approaches for preparation of stalled ribosomal complexes for cryo-electron microscopy studies.